Molecular Pathogenesis of Gut Microbiome Associated Colorectal Cancer: Recent Updates - Akansha Yadav; Rajendra Prakash Maurya; Akhilendra Kumar Maurya (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Background: Colorectal cancer (CRC) incidence and mortality vary distinctly around the world. It is the second most commonly diagnosed cancer in females and third in males while it ranked second in cancer-related deaths globally. Mutational landscape including chromosomal damage and microsatellite instability enabled to insignificant weightage about the survival of patients and their therapeutic response against CRC. Root cause of colorectal carcinogenesis has traditionally based on genetic alterations; however, in broader sense CRC advances as a result of complex communications between the microbiota, host mucosa, aberrant signaling, dietary components and inflammatory mediators. Additionally, it has increased risks combined with inflammatory bowel disease. Possible mechanism associated with CRC and microbial dysbiosis includes various bacterial signatures expose colonic mucosa via different metabolic and inflammatory stimuli, producing a proinflammatory state enabling DNA damage, aberrant signaling and ultimately CRC. Objective: The objective of this study was to investigate the role of gut microbiota in CRC pathogenesis in light of recent updates. Methods: PubMed and google scholar databases and carried out selective literature review on contribution of gut microbiota and associated mechanism in pathogenesis of CRC. Results: Under normal conditions gut microbiome act as barrier to other pathogens or infection in gastrointestinal tract but studies suggest change in microbial composition related to CRC progression. Imbalance in microbial composition is related with inflammation induced tumorigenesis and modulation of anti-cancer immune response. Thus, gut microbiota can be used as biomarkers for early diagnosis and predict the effect of immunotherapy. Conclusion: This review is focused on to dissect the role of intestinal microbiota and metabolites, signaling molecules and pro-inflammatory factors that directly or indirectly influencing the molecular carcinogenesis ultimately leading to CRC development. The recent updates will be benefited to many translational researchers as well as clinicians.